Muslimah design trends through the role of fashion forecasting / Suriati Saidan ... [et al.] - Saidan, Suriati; Saaidin, Husna; Wan Kamarulbaharin, Wan Nadhra Ixora; Zainun, Norzaleha; Adzmi, Mohd Hafnidzam (Universiti Teknologi MARA, Perak, 2022)
Muslimah fashion design nowadays is a fashion trend that is the best alternative for Muslim women who want to cover their aurat with an attractive style. With a variety of options, Islamic clothing is not considered conservative or outdated. Therefore, the form of fashion design should be more contemporary and in accordance with Islamic characteristics and suitable for use by all nations. In this paper the researcher will look at the fashion forecasting process used in the production of Muslimah clothing. Fashion trends are an important element in determining the concept of clothing design. As a trend forecasting concept, several things have a significant impact on the fashion industry. The ability to forecast trends in fashion, technology, and culture is a critical area of the marketing industry dedicated to identifying patterns of consumer behavior while helping companies and brands connect with audiences. Fashion trends are styles of clothing and accessories that are popular at a particular time. It will affect the popularity and lifestyle for example through the use of colors and fabrics used. Fashion forecasters will do research somewhere to find out new trends and try to bring some new ideas about the brand. It requires scientific skills and creative concepts. Thus, fashion forecasting is a field in the fashion industry that is concerned with predicting upcoming fashion trends in terms of colors, design techniques, textile materials, and more that lead to consumer demand. Fashion forecasters produce trend reports that are used to develop a brand for the production of a product. In the process of making designs, designers need to pay attention to fashion predictions which in addition to having Islamic characteristics, the design can be comparable to international designs.